Effectiveness of ultrasonic activation associated to glycolic acid on smear layer removal, dentin structure and bond strength to root dentin - Matheus Albino Souza; Julia Pommer dos Santos; Luanda Tissiani; Uillian Rauch Magalhães; Karolina Frick Bischoff; Rafaela Ricci; Laura Teixeira Hoffmann; Paula Cristine Ghiggi; João Paulo De Carli; Juliane Bervian; Eduardo Gonçalves Mota; José Antonio Poli de Figueiredo; et al. (Bioscience Journal, 2023)
This study evaluated the effects of ultrasonic activation (US) associated to glycolic acid (GA) on smear layer, dentin structure and bond strength (BS) of filling/restorative material to root dentin. The roots were used for antimicrobial activity, dentin structure and BS evaluation, being distributed into seven groups, according to irrigation protocols: G1:DW+US; G2:17% EDTA; G3:QMix; G4:17% GA; G5:17% EDTA+US; G6:QMix+US; G7:17% GA+US. Scanning electronic microscopy, transmission electronic microscopy and push-out were performed, with specific statistical analysis for each evaluation. The highest smear layer removal occured in Groups 6 and 7 (p<0.05), and the largest collagen dispersion in Group 7, being similar to Group 2 and 5 (p>0.05). The highest BS of filling and restorative material occurred in Groups 6 and 7, and Groups 5, 6 and 7, respectively, being similars between them (p>0.05). The use of GA+US promoted effective smear layer removal and dentin structure preservation, improving the BS of filling/restorative material to root dentin.